Exploratory Data Analysis in Data Mining Classification Task - Wahyuni, Eka Dyar; Arifiyanti, Amalia Anjani; Kustyani, Mashita (ReTII, 2019)
Each type of data has various forms and behaviors. Therefore, the process of data analysis cannot be standardized through a certain procedure. EDA is a data analysis approach that can be used in interpreting the information contained in data. EDA is flexible in adjusting data behavior and can be used for data observation through various points of view. This data analysis strategy can be used to complement the results of data mining classification analysis used to recognize data patterns. In this article it will be explained that EDA can help in enriching the results of data analysis and assist in the pre-processing stages of data mining classification. Data mining classification is done using the Naive Bayes Classifier algorithm and Logistic Regression.